Case Study of Spatial Planning Mismatch Against Geomorphology in Kampar Regency: Landslide Susceptibility Analysis - Aisyah Ajad; Tengku Hamzah, Tengku Adeline Adura; Bayu Wijayanto; Asep; Aprizon Putra (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
This research performs a comprehensive landslide hazard mapping in Kampar Regency by integrating Geographic Information System (GIS) technology with a weighted overlay modeling approach based on four critical physical parameters: slope gradient, rainfall intensity, soil type erodibility, and land use characteristics. Utilizing classification standards from BAPPEDA and weighting methods from Taufik Q, Firdaus et al. (2012) and BNPB Regulation No. 02 of 2012, the study identifies that the region is dominated by rainfall intensities of 2501–3000 mm/year and a significant distribution of Andosol soil types which contribute to soil instability. The spatial analysis results categorize the hazard levels into three classes—Safe, Moderately Prone, and Prone—revealing that XIII Koto Kampar Subdistrict faces the highest risk with a prone area of 88,008.48 hectares (92.36%), primarily due to steep topography and high runoff velocity, whereas Bangkinang Subdistrict is identified as the safest area with a low-risk coverage of 6,836.66 hectares (28.20%). These findings conclude that land use with high vegetation density, such as forests which cover 73,154.26 hectares, plays a vital role in reducing runoff, and the resulting hazard map serves as a crucial spatial decision-support tool for disaster mitigation and regional planning in Kampar Regency.